Financial Options as Determinants of Sports Facility Development in Lagos State, Nigeria (2007)
This research was carried out to look into Financial Options policy as determinants of sport development in Lagos State, Nigeria. It was in realization that huge financial investments are now needed to manage sports or to build new state of the art sporting arenas costing anywhere between N30 billion Naira. There are many options in financing sport and recreational facilities that involve both public and private arrangements and investments. This study looked into various finance ventures, as well as benefits and pitfalls of those options. In the study funding is separated into two distinct groups, public funding and private funding. A descriptive survey research method was adopted for the study while purposive sampling techniques was used to select 530 respondents from the population. Inferential statistics of multiple regressions was used to test the hypothesis at 0.05 level of significance, conclusion and recommendations were also drawn at the end of the study